The Internet's Transformative Power on Journalism Culture in Greece: Looking beyond universal professional values. Issue 2 (7th February 2017) - Touri, Maria; Theodosiadou, Sophia; Kostarella, Ioanna
Abstract : News and journalism practices are undergoing complex changes under the influence of technology. As the internet facilitates new ways of collecting and reporting information, conceptions of journalistic identity based on normative values such as objectivity, impartiality and gatekeeping are being contested. These ideals have become a central reference point in empirical evaluations of technological innovations in journalism cultures. However, as they are engrained in Western models of news production, they often mask the nuances that exist in the appropriation of the internet in different locales. In order to offer a better understanding of online technologies as they are adapted in different cultures, online journalism research can benefit from more conceptual clarity in defining journalism culture. We argue that such clarity can assist in capturing the complexity of online journalism as the outcome of profound changes taking place in different societies. We aim to contribute to current debates by borrowing an existing theoretical conceptualization of journalism culture to explore online journalism in Greece. Through interviews with professional journalists, we show the nuances of online journalism as this evolves through a dynamic interaction between technology and local contingencies in a climate of financial uncertainty.